Synthesis of Bicyclic Thiazolidinethiones and Oxazolidinones by Water‐Mediated Multicomponent Reactions (MCR) and Ring‐Closing Metathesis (RCM)1. Issue 35 (11th October 2013) - Stalling, Timo; Saak, Wolfgang; Martens, Jürgen
Abstract: Starting with the development of new multicomponent reactions (MCR) in water, hydroxy thiazolidinethiones and oxazolidinones were prepared efficiently in a one‐pot procedure. The reaction was carried out under mild conditions, consistent with the principles of "green chemistry". These precursors were converted into different dienes containing terminal C–C double bonds by modifying the hydroxy group in one‐ or two‐step sequences. A final ring‐closing metathesis (RCM) reaction led to various classes of unsaturated bicycles. Abstract : New multicomponent reactions (MCR) were developed to form hydroxy thiazolidinethiones and oxazolidinones in one‐pot procedures under mild conditions using water as solvent. The hydroxy group was functionalized to give terminal dienes. These species were transformed into unsaturated bicycles containing different carbocyclic and heterocyclic elements by ring‐closing metathesis (RCM).